Effect of salt and organic acid on storage quality of minimally processed Indian spinach: Storage quality of minimally processed spinach (Journal of the Bangladesh Agricultural University, 2019)
Postharvest processing of horticultural products not only adds value to the products, but also makes the products more convenient to the consumers. The objective of this study was to investigate the storage quality of minimally processed Indian spinach as influenced by organic acid and salt. The vegetables were washed and immersed in cold (7ºC) water with 100 mg L-1 free chlorine for sanitation. The samples were treated with NaCl, KMS and citric acid in 9 treatments viz. T1: 1% NaCl, T2: 1.5% NaCl, T3: 2% NaCl, T4: 1.5% citric acid, T5: 1% citric acid, T6: 0.5% citric acid, T7: 0.5% KMS, T8: 1% KMS and T9: 1.5% KMS. The treated samples were stored for 0 to 6 days. Among the treatments, changes in quality traits decreased significantly (p = 0.05) with the increasing rate of organic acid (T4) compared to the control and other treatments during the storage period. Treatment T4 was better than other treatments as the treated spinach had higher titrable acidity (33.47, 22.60 & 18.83), lower TSS (0.30, 0.30 & 0.40), lower pH (6.99, 3.43 & 4.12), higher vitamin C (17.03, 16.33 & 11.40), lower weight loss (10, 9.90 & 9.40) and higher firmness (15.45, 13.29 & 10.67) at 2, 4 and 6 days. The storage ability was good for all treatments, but keeping quality was not satisfactory for all treatments. There was significant variation among all treatments, and 1.5% citric acid was accepted for keeping the good storage quality of minimally processed Indian spinach.J. Bangladesh Agril. Univ. 17(1): 99–104, March 2019